La qualité des plages au cœur des enjeux de développement : La situation des îles de l’océan Indien - Virginie Duvat (EchoGéo)
Today, the quality of the tropical beaches is closely linked to development challenges for two main reasons. At first, because sandy beaches play an important role in tourism development policies, and secondly because of the emergence of the touristic and recreative activities of the local communities. In this context, the purpose of this paper is to expose the results of an assessment which was done in the Seychelles and Mascarene islands and to highlight the relationship which can be observed between beach quality, natural assets and the strategies of public and private actors.